Plasma Branched-Chain Amino Acids Are Associated With Greater Fasting and Postprandial Insulin Secretion in Non-diabetic Chinese Adults - Ding, Cherlyn; Egli, Leonie; Bosco, Nabil; Sun, Lijuan; Goh, Hui Jen; Yeo, Khung Keong; Yap, Jonathan Jiunn Liang; Actis-Goretta, Lucas; Leow, Melvin Khee-Shing; Magkos, Faidon (Frontiers in Nutrition, 2021)
Abstract Background: Plasma branched-chain amino acids (BCAA) are consistently elevated in subjects with obesity and type 2 diabetes (T2DM) and correlate with insulin resistance. The association of BCAA with insulin secretion and clearance rates has not been adequately described. Objective: To evaluate the relationships between fasting and postprandial plasma BCAA, insulin secretion and insulin clearance. Design: 95 non-diabetic Chinese subjects (43 females) underwent a mixed-meal tolerance test; blood biomarkers including BCAAs (leucine, isoleucine, valine) were measured for 6 hours. Fasting and postprandial insulin secretion rates (ISR) and insulin clearance were determined by oral minimal modeling of glucose and C-peptide. Results: Fasting and postprandial plasma BCAA correlated strongly with each other (ρ = 0.796, P < 0.001), and both were positively associated with basal ISR (ρ = 0.45/0.36, P < 0.001), total postprandial ISR AUC (ρ = 0.37/0.45, P < 0.001), and negatively with insulin clearance (ρ = -0.29/-0.29, P < 0.01), after adjusting for sex and body mass index. These relationships largely persisted after adjusting further for insulin resistance and postprandial glucose. Compared with subjects in the middle and lowest tertiles for fasting or postprandial plasma BCAA, subjects in the highest tertile had significantly greater postprandial glucose (by 7-10%) and insulin (by 74-98%) concentrations, basal ISRs (by 34-53%), postprandial ISR AUCs (by 41-49%), and lower insulin clearance rates (by 17-22%) (all P < 0.05). Conclusions: Fasting and postprandial plasma BCAA levels are associated with greater fasting and postprandial insulin secretion and reduced insulin clearance in healthy Chinese subjects. These observations potentially highlight an additional layer of involvement of BCAA in the regulation of glucose homeostasis.